2021
DOI: 10.1177/09500170211021568
|View full text |Cite
|
Sign up to set email alerts
|

Working Hard for the Ones You Love and Care for Under Covid-19 Physical Distancing

Abstract: In 2020, Covid-19 was spreading quickly in nursing homes, leading to numerous challenges for care workers. We tell the story of Marieke, a devoted female care assistant working in a Belgian nursing home that is customer-centred in their organisational model. Her narrative provides poignant insights into the ‘work and life’ struggles and conflicts of a female care assistant facing the challenges of this model during the Covid-19 pandemic, which has left the largely female care workforce widely exposed to the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Although reporting similar themes, our study offers a more thorough and comprehensive view with its unambiguous focus on the experiences of care aides and our larger sample size. Previous studies with care aides outline pandemic hardships, [23][24][25] but not coping mechanisms. We uniquely identified that care aides used coping strategies such as spirituality, peer support, and teamwork.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although reporting similar themes, our study offers a more thorough and comprehensive view with its unambiguous focus on the experiences of care aides and our larger sample size. Previous studies with care aides outline pandemic hardships, [23][24][25] but not coping mechanisms. We uniquely identified that care aides used coping strategies such as spirituality, peer support, and teamwork.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with care aides outline pandemic hardships, 23–25 but not coping mechanisms. We uniquely identified that care aides used coping strategies such as spirituality, peer support, and teamwork.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Här upplevdes framför allt låga nyckeltal i personalen och oro för både boendes och egna anhörigas liv som de största källorna till stress. För att kunna uppnå fortsatt hög kvalitet i servicen kompenserade personalen för organisationens personalbrist genom att ta på sig ett ökat omvårdnadsansvar (Vermeerbergen et al, 2021, se också Selberg, 2013.…”
Section: A R T I K E Lunclassified